2019
DOI: 10.3389/fmicb.2019.00736
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Polymeric Substances Acting as a Permeable Barrier Hinder the Lateral Transfer of Antibiotic Resistance Genes

Abstract: Antibiotic resistance genes (ARGs) in bacteria are emerging contaminants as their proliferation in the environment poses significant threats to human health. It is well recognized that extracellular polymeric substances (EPS) can protect microorganisms against stress or damage from exogenous contaminants. However, it is not clear whether EPS could affect the lateral transfer of ARGs into bacteria, which is one of the major processes for the dissemination of ARGs. This study investigated the lateral transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Owing to such a possible protective pathway, the bloom of ARGs did not occur, even when exposed to high concentrations of SDZ. On the other hand, a previous study showed that Ca 2+ could electrostatically bind with the function groups of EPS, consequently, the bridge between plasmids and EPS was established (Hu et al, 2019). This bond could impede the horizontal transfer of plasmid-borne ARGs into recipient cells (Hu et al, 2019).…”
Section: Protective Mechanismsmentioning
confidence: 96%
“…Owing to such a possible protective pathway, the bloom of ARGs did not occur, even when exposed to high concentrations of SDZ. On the other hand, a previous study showed that Ca 2+ could electrostatically bind with the function groups of EPS, consequently, the bridge between plasmids and EPS was established (Hu et al, 2019). This bond could impede the horizontal transfer of plasmid-borne ARGs into recipient cells (Hu et al, 2019).…”
Section: Protective Mechanismsmentioning
confidence: 96%
“…Resistance and survival, even in adverse conditions, help microbes colonize in various implantable materials, such as dental implants and catheters [100] . Most organisms in a biofilm are protected by the EPS layers and are resistant to various antimicrobial drugs [79] , [117] , [118] . The glycocalyx can trap antibacterial drugs at their maximum capacity, reducing the effectiveness of the drugs against the organisms present in a biofilm as well as plays an antimicrobial role [30] , [118] .…”
Section: Biofilms In Public Healthmentioning
confidence: 99%
“…The increased resistance to antimicrobial drugs or agents compared to planktonic cells is the emergent property of a biofilm. The biomass can be considered a fortress in which the antimicrobial tolerance and survival of desiccation form buttresses [58]. The EPS in a biofilm can quench the activity of antimicrobial agents that transfer into the biofilm in a form of suppression known as diffusion-reaction inhibition.…”
Section: The Components and Structure Of Biofilmsmentioning
confidence: 99%